Perceraian dan Akibat Hukumnya di Negara Muslim: - Agung Burhanusyihab; KM Al Fathur Ikhsan (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
Building a joyful and eternal family (home) based on the One Godhead is one of marriage's objectives. The cornerstone of the home's integrity, however, is threatened by issues that arise between the husband and wife when managing the household. There must be specific grounds given to the court in the event of a divorce between the two parties. Divorce has repercussions on many levels, including the influence on children, shared marital property, and guardianship. This study aims to investigate the effects of divorce in each Muslim nation in more detail. This study draws on literature reviews of books and articles that are relevant to the topic as well as various studies that address the effects of the effects of divorce in different Muslim nations. Keywords: Divorce, Legal Repercussions, Muslim Countries.